1995
DOI: 10.1051/lait:1995318
|View full text |Cite
|
Sign up to set email alerts
|

Separation of casein hydrolysates using polysulfone ultrafiltration membranes with pH and EDTA treatments applied

Abstract: Summary -The preparation of peptide fractions from case in hydrolysates can be achieved by the use of ultrafiltration for the removal of the enzyme from the reaction mixture and/or to obtain specifie fractions of peptides. However, the ultrafiltration of case in hydrolysates is subjected to severe fouling phenomena which affect both the flux decline and the rejection properties of the membrane. Polysulfone membrane material used in previous work showed specifie rejection properties towards charged or hydroxyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Normally, J increased with the membrane MWCO for a given material (PES or m-PES); PES membranes appeared markedly less permeable than m-PES and PS ones probably because of the stronger hydrophobic nature of PES. Highest permeation fluxes were thus obtained with the 8 kDa PS membrane (80 L h À1 m À2 , at 2 bar and 60°C), a value comparable with those obtained by Gourley et al (1995) for the ultrafiltration of a casein hydrolysate in similar conditions (about 60 L h À1 m À2 for a 10 kDa membrane, and 35 L h À1 m À2 for a 5 kDa PS one).…”
Section: Permeation Fluxsupporting
confidence: 79%
See 1 more Smart Citation
“…Normally, J increased with the membrane MWCO for a given material (PES or m-PES); PES membranes appeared markedly less permeable than m-PES and PS ones probably because of the stronger hydrophobic nature of PES. Highest permeation fluxes were thus obtained with the 8 kDa PS membrane (80 L h À1 m À2 , at 2 bar and 60°C), a value comparable with those obtained by Gourley et al (1995) for the ultrafiltration of a casein hydrolysate in similar conditions (about 60 L h À1 m À2 for a 10 kDa membrane, and 35 L h À1 m À2 for a 5 kDa PS one).…”
Section: Permeation Fluxsupporting
confidence: 79%
“…The main applications concern dairy products ( Gourley et al, 1995;Daufin et al, 1998), vegetable substrates such as gliadin (Bérot et al, 2001), soy protein (Deeslie and Cheryan, 1991), or animal ones such as hemoglobin (Sannier et al, 1996). Regarding fish hydrolysates, only a few works dealing with the development of a concentration or fractionation process have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A positive value indicates a more hydrophobic character of a particular amino acid sequence. Interestingly, almost all peptides that were adsorbed at pH 9 have a positive GRAVY score except for peptides ␤-LG 9-14 (10) and 125-138 (15). At pH 9, it seems that a balance between electrostatic (attractive) and hydrophobic interactions with the G-10 membrane seems necessary for the peptides to be adsorbed.…”
Section: Effect Of Caclmentioning
confidence: 99%
“…Many studies about peptide fractionation by UF or NF have shown higher flux reduction when performing filtration at acid pH as compared to basic pH due to the development of a more important hydraulic resistance associated with fouling [10][11][12]15]. Most of the peptides released upon hydrolysis of milk proteins are acid or neutral since these proteins have a pI between 4 and 6 [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Membrane separation technologies and in particular ultrafiltration (UF) have already been used to fractionate protein hydrolysates (Gourley et al, 1995;Nau et al, 1995;Pouliot and Gauthier, 1990;Visser et al, 1989). These works suggest the crucial role of membrane peptides ionic interactions to separate components with close molecular weights (MW) but different net charges.…”
Section: Introductionmentioning
confidence: 99%